2016
DOI: 10.1371/journal.pone.0167623
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Incidence of Cardiovascular Diseases and All-Cause Mortality in a Middle Eastern Population over a Decade Follow-up: Tehran Lipid and Glucose Study

Abstract: BackgroundTo examine the association between potentially modifiable risk factors with cardiovascular disease (CVD) and all-cause mortality and to quantify their population attributable fractions (PAFs) among a sample of Tehran residents.MethodsOverall, 8108 participants (3686 men) aged≥30 years, were investigated. To examine the association between risk factors and outcomes, multivariate sex-adjusted Cox proportional hazard regression analysis were conducted, using age as time-scale in two models including gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 69 publications
4
59
0
Order By: Relevance
“…Aging and population growth, as well as improvements in life expectancy and other health indicators, will have a major influence on the region's health and resources, particularly among low‐ and middle‐income countries, such as Iran . It is worth noting the high prevalence, morbidity and mortality of cardiovascular diseases (CVD) in general and in older populations in Iran and the Middle East …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging and population growth, as well as improvements in life expectancy and other health indicators, will have a major influence on the region's health and resources, particularly among low‐ and middle‐income countries, such as Iran . It is worth noting the high prevalence, morbidity and mortality of cardiovascular diseases (CVD) in general and in older populations in Iran and the Middle East …”
Section: Introductionmentioning
confidence: 99%
“…2 It is worth noting the high prevalence, morbidity and mortality of cardiovascular diseases (CVD) in general and in older populations in Iran and the Middle East. [3][4][5][6] Many studies have shown trends in CVD risk factors in general populations in most regions of the world, but there are few studies in older populations. 7 It is therefore difficult to generalize the efficacy of preventive programs to this group.…”
Section: Introductionmentioning
confidence: 99%
“…At present, 15% to 30% of the patients who undergo coronary artery surgery are diabetic 8789 . During cardiac surgery, the heart is inevitably subjected to I/R injury due to pre-existing coronary occlusion and heart arrest subsequent to aortic artery cross-clamp.…”
Section: Challenges Of Remote Ischemic Conditioning In Diabetic Cardimentioning
confidence: 99%
“…CVD is the number one causes of death in the United States with 1 in every 4 death are attributed to CVD [7]. Modifiable risk factors, such as being overweight and obese account for more than 70% of the risk for CVD and mortality caused by CVD.…”
Section: Introductionmentioning
confidence: 99%